2017
DOI: 10.4103/0971-4065.202839
|View full text |Cite
|
Sign up to set email alerts
|

Primary renal echinococcosis

Abstract: Echinococcosis is a parasitic infection caused by the larval stage of a cestode Echinococcus granulosus and is endemic in sheep farming regions of developing countries. It manifests as hydatid cyst and most commonly is found in liver followed by lungs. Renal hydatid cyst is rare and amounts for 2% of all cases. There are no specific clinical manifestations, and hence diagnosis of renal hydatid disease is missed out easily without imaging. We report a case of 50-year-old female who had 6 months history of lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…The cyst may become large enough to destroy the tissues of the host. Renal hydatid cyst is rare and accounts for 2% of all hydatid cyst cases [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cyst may become large enough to destroy the tissues of the host. Renal hydatid cyst is rare and accounts for 2% of all hydatid cyst cases [12].…”
Section: Discussionmentioning
confidence: 99%
“…In this case abdominal pain was reported but in our case, flank pain was notable. She had right renal hydatid cyst on imaging which was treated with right nephrectomy and albendazole treatment regimen before and after operation [ 12 ]. Kumar et al [ 18 ] reported a 37-year-old female patient with right iliac fossa pain.…”
Section: Discussionmentioning
confidence: 99%
“…Isolated intra-renal-pelvic hydatid cyst possibly develops when a small renal parenchymal hydatid cyst communicates with the pelvicalyceal system and subsequently grows within the pelvicalyceal system. [ 5 ]…”
Section: Discussionmentioning
confidence: 99%
“…On USG, renal hydatid cysts have variable appearance presenting either as unilocular cysts, multiseptated cysts or calcified cysts. [ 1 5 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation